Empowerment of Housewives through Compost Making Training for Organic Waste Management using the Takakura Method in Bebandem Village, Karangasem - Ahmad Alfito Dinova; Gusti Ayu Hista Werastiari (Journal of Social Research, 2025)
The increasing volume of organic waste in Bebandem Village, Karangasem, is a serious problem due to the lack of understanding of housewives in managing it independently. As a solution, the PPK Ormawa KSR-PMI Team of Udayana University held an empowerment program through the Prabu Literacy Corner, which provided training and assistance in making compost using the Takakura method to 39 housewives. This activity was carried out in ten structured meeting sessions that included socialization, direct practice, and evaluation to ensure skill mastery. The results of the program showed a significant increase, where 100% of participants were now able to sort waste (an increase of 60.53%) and 100% of participants managed to master Takakura composting skills. The final achievement rate of the activity reached 96.91% with the category "Excellent". This training succeeded in increasing community independence in processing waste from its source and converting organic waste into value-added compost, as well as fostering concern for the environment.